Задание №1
![\frac{x+4}{x^{2}+5x+4}=\frac{(x+4)}{(x+1)(x+4)}=\frac{1}{x+1} \frac{x+4}{x^{2}+5x+4}=\frac{(x+4)}{(x+1)(x+4)}=\frac{1}{x+1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B4%7D%7Bx%5E%7B2%7D%2B5x%2B4%7D%3D%5Cfrac%7B%28x%2B4%29%7D%7B%28x%2B1%29%28x%2B4%29%7D%3D%5Cfrac%7B1%7D%7Bx%2B1%7D)
------------------------------------------------------------------------------------------
![\frac{x^{2}-3x-18}{x-6}=\frac{(x-6)(x+3)}{(x-6)}=x+3 \frac{x^{2}-3x-18}{x-6}=\frac{(x-6)(x+3)}{(x-6)}=x+3](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D-3x-18%7D%7Bx-6%7D%3D%5Cfrac%7B%28x-6%29%28x%2B3%29%7D%7B%28x-6%29%7D%3Dx%2B3)
------------------------------------------------------------------------------------------
![\frac{x^{2}-4}{x^{2}-5x+6}=\frac{(x+2)(x-2)}{(x-3)(x-2)}=\frac{x+2}{x-3} \frac{x^{2}-4}{x^{2}-5x+6}=\frac{(x+2)(x-2)}{(x-3)(x-2)}=\frac{x+2}{x-3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D-4%7D%7Bx%5E%7B2%7D-5x%2B6%7D%3D%5Cfrac%7B%28x%2B2%29%28x-2%29%7D%7B%28x-3%29%28x-2%29%7D%3D%5Cfrac%7Bx%2B2%7D%7Bx-3%7D)
------------------------------------------------------------------------------------------
![\frac{x^{2}+10x+21}{x^{2}-9}=\frac{(x+3)(x+7)}{(x+3)(x-3)}=\frac{x+7}{x-3} \frac{x^{2}+10x+21}{x^{2}-9}=\frac{(x+3)(x+7)}{(x+3)(x-3)}=\frac{x+7}{x-3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%2B10x%2B21%7D%7Bx%5E%7B2%7D-9%7D%3D%5Cfrac%7B%28x%2B3%29%28x%2B7%29%7D%7B%28x%2B3%29%28x-3%29%7D%3D%5Cfrac%7Bx%2B7%7D%7Bx-3%7D)
================================================================
Задание № 2
![\frac{10x^{2}-6x+5xb-3b}{5x^{2}-8x+3}=\frac{(10x^{2}-6x)+(5xb-3b)}{(5x-3)(x-1)}=\frac{2x(5x-3)+b(5x-3)}{(5x-3)(x-1)}=\frac{(5x-3)(2x+b)}{(5x-3)(x-1)}=\frac{2x+b}{x-1} \frac{10x^{2}-6x+5xb-3b}{5x^{2}-8x+3}=\frac{(10x^{2}-6x)+(5xb-3b)}{(5x-3)(x-1)}=\frac{2x(5x-3)+b(5x-3)}{(5x-3)(x-1)}=\frac{(5x-3)(2x+b)}{(5x-3)(x-1)}=\frac{2x+b}{x-1}](https://tex.z-dn.net/?f=%5Cfrac%7B10x%5E%7B2%7D-6x%2B5xb-3b%7D%7B5x%5E%7B2%7D-8x%2B3%7D%3D%5Cfrac%7B%2810x%5E%7B2%7D-6x%29%2B%285xb-3b%29%7D%7B%285x-3%29%28x-1%29%7D%3D%5Cfrac%7B2x%285x-3%29%2Bb%285x-3%29%7D%7B%285x-3%29%28x-1%29%7D%3D%5Cfrac%7B%285x-3%29%282x%2Bb%29%7D%7B%285x-3%29%28x-1%29%7D%3D%5Cfrac%7B2x%2Bb%7D%7Bx-1%7D)
-------------------------------------------------------------------------------------------
![\frac{2x^{2}-10x-xb+5b}{3x^{2}-14x-5}=\frac{(2x^{2}-10x)+(-xb+5b)}{(x-5)(3x+1)}=\frac{(2x^{2}-10x)-(xb-5b)}{(x-5)(3x+1)}=\frac{2x(x-5)-b(x-5)}{(x-5)(3x+1)}=\frac{(x-5)(2x-b)}{(x-5)(3x+1)}=\frac{2x-b}{3x+1} \frac{2x^{2}-10x-xb+5b}{3x^{2}-14x-5}=\frac{(2x^{2}-10x)+(-xb+5b)}{(x-5)(3x+1)}=\frac{(2x^{2}-10x)-(xb-5b)}{(x-5)(3x+1)}=\frac{2x(x-5)-b(x-5)}{(x-5)(3x+1)}=\frac{(x-5)(2x-b)}{(x-5)(3x+1)}=\frac{2x-b}{3x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E%7B2%7D-10x-xb%2B5b%7D%7B3x%5E%7B2%7D-14x-5%7D%3D%5Cfrac%7B%282x%5E%7B2%7D-10x%29%2B%28-xb%2B5b%29%7D%7B%28x-5%29%283x%2B1%29%7D%3D%5Cfrac%7B%282x%5E%7B2%7D-10x%29-%28xb-5b%29%7D%7B%28x-5%29%283x%2B1%29%7D%3D%5Cfrac%7B2x%28x-5%29-b%28x-5%29%7D%7B%28x-5%29%283x%2B1%29%7D%3D%5Cfrac%7B%28x-5%29%282x-b%29%7D%7B%28x-5%29%283x%2B1%29%7D%3D%5Cfrac%7B2x-b%7D%7B3x%2B1%7D)